Determinants of Food Security in Nigeria - Enilolobo, O. S.; Nnoli, T. I.; Olowo, S. O.; Aderemi, Timothy Ayomitunde; Adewole, A. O.; Olapade, V. O.; Esedeke, J. F. (Acta Universitatis Danubius. Œconomica, 2022)
The aim of this study is to examine the determinants of food security in Nigeria. In this study, a multiple regression model was specified, which captured the effects of labour input (measured using employment in the agricultural sector), domestic capital investment (measured using gross fixed capital), bank inclusion (measured using bank lending to agriculture), environmental quality (measured using percentage of carbon dioxide emission to gross national income, and oil revenue. The autoregressive distributed lag (ARDL) method was adopted for analyzing the model, while pairwise granger causality was used to provide robust results. The results from the regression estimates found that only domestic capital had significant positive impact on food security in Nigeria; whereas bank lending only had significant positive impact on food security in Nigeria during the short run period. Based on the results the study recommends that: the Nigerian government should provide a conducive environment in the agricultural sector, for private participation; the CBN needs to look into bank lending policies and iron out gray areas that inhibit bank lending to the agricultural sector; the CBN, the Federal Ministry for Agriculture, the Ministry of Finance and the private sector should convey and design a short-long term plan for the growth and development of the agricultural sector in Nigeria; it is important to make agricultural subject a compulsory one in secondary schools; and the Nigerian government should reduce dependence on non-renewable energy.